2020
DOI: 10.22603/ssrr.2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

New Method for the Quantitative Assessment of Sensory Disturbances in Cervical Myelopathy: Application for Neurological Level Diagnosis

Abstract: Introduction: Cervical myelopathy frequently manifests as sensory disturbances, including numbness, and their distribution pattern aids in neurological level diagnosis. However, the objective assessment of sensory disturbances is challenging. In this study, we attempted to quantitatively evaluate sensory symptoms in patients with cervical myelopathy according to lesion level using PainVision ®. Methods: Dermal sensations were evaluated in patients (n = 158) and healthy volunteers (n = 100) using PainVision ® P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Inoue et al reported that there was no correlation between the CPT measured with the PainVision TM system and the VAS score in cervical myelopathy patients (n = 158) or healthy volunteers (n = 100). However, the CPT showed significant associations with other variables, including the Japanese Orthopaedic Association (JOA) score, the JOA cervical myelopathy evaluation questionnaire (JOAMEQ), and the quality of life [32]. Kim et al reported that although there was a significant correlation between the QPD and MPQ, there was no correlation between the QPD and VAS (Spearman rank correlation coefficients = 0.240, p = 0.248) [31].…”
Section: Validity Of Electrical Parameters As Quantitative Diagnostic...mentioning
confidence: 99%
“…Inoue et al reported that there was no correlation between the CPT measured with the PainVision TM system and the VAS score in cervical myelopathy patients (n = 158) or healthy volunteers (n = 100). However, the CPT showed significant associations with other variables, including the Japanese Orthopaedic Association (JOA) score, the JOA cervical myelopathy evaluation questionnaire (JOAMEQ), and the quality of life [32]. Kim et al reported that although there was a significant correlation between the QPD and MPQ, there was no correlation between the QPD and VAS (Spearman rank correlation coefficients = 0.240, p = 0.248) [31].…”
Section: Validity Of Electrical Parameters As Quantitative Diagnostic...mentioning
confidence: 99%
“…They experienced the VR presentations while lying at in the same position as the patients who underwent the surgical procedure. Their pain thresholds were measured using a PainVision® PS-2100 (Nipro Corporation, Osaka, Japan) to measure the level of electric current perceived as pain 10,11) . Measurements were conducted to determine: (1) the minimal perceived current (without VR); (2) the current while experiencing the natural landscape VR; and (3) the current while experiencing the video game VR.…”
Section: Vr Presentationsmentioning
confidence: 99%
“…This ability of the sinusoidal waveform to preferentially stimulate different nerve fibers has been incorporated in a technique called Current Perception Threshold (CPT), which consists on applying sinusoidal current waves by means of superficial electrical stimulation at 2KHz, 250 Hz, and 5 Hz and registering their associated sensory or perception thresholds 8,9 . CPT has been proven successful for the early diagnosis of diabetic neuropathies 13,14 and other types of pathologies such as cervical myelopathy or urinary tract dysfunction among others 10,15–17 . Painless normative CPT thresholds have been established recently in the literature for various cutaneous and/or mucosal sites of the body and the correlation of these thresholds with stimulation frequency, sex, age, and body fat has been demonstrated 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 CPT has been proven successful for the early diagnosis of diabetic neuropathies 13,14 and other types of pathologies such as cervical myelopathy or urinary tract dysfunction among others. 10,[15][16][17] Painless normative CPT thresholds have been established recently in the literature for various cutaneous and/or mucosal sites of the body and the correlation of these thresholds with stimulation frequency, sex, age, and body fat has been demonstrated. [18][19][20] CPT is usually applied by means of transcutaneous round electrodes of 10 mm of diameter; however, other specific types of electrodes have been also proposed to achieve a selective stimulation of nociceptive fibers (thin Aδ, C fibers).…”
Section: Introductionmentioning
confidence: 99%